Retardo de crecimiento intrauterino simétrico y asimétrico en los recién nacidos asistidos en el servicio de neonatología del Hospital Regional Isidro Ayora - Galarza Sigüenza, Jenny Silvana (2015)
Intrauterine growth restriction (IUGR) is an important cause of perinatal morbidity and mortality, for that it has been convenient to make this investigation determining the prevalence and causes of symmetrical and asymmetrical intrauterine growth retardation. This research is retrospective, descriptive, qualitative, and quantitative, and transverse, it was made in newborns assisted in the Neonatology Service of the Isidro Ayora Regional Hospital in 2013. For the development it was used Battaglia and Lubchenco Curves and a data collection sheet which information was obtained from the medical histories ; finding that of the 3018 of newborns attended: 61 have intrauterine growth restriction or low weight for gestational age of which 75 % have asymmetric IUGR and 25% they are symmetrical, having as most important causes the maternal age between 15 - 21 years with 43 % , the highest percentage was found urinary tract infection during pregnancy with 95 %, prenatal controls < 5 with 18.3 % and chronic disease with prevalence of hypertension with 30% , according to fetal causes the highest percentage was threatened abortion with a 50 %, a 23.3 % premature rupture of membranes and 3.3% genetic diseases in which Down syndrome was found; determining that the causes or risk factors found , are preventable in their most percentage. Keywords: intrauterine growth retardation, newborns, pregnant women , maternal and fetal causes.